Teachers' professional learning revealed in lesson study research - Richit, Adriana [UNESP] (2021)
Originating in Japan, the lesson study (jugyo kenkyu) is a collaborative and reflective teacher professional development process, centered on the teaching practice. Due to its development dynamics and possibilities to promote professional learning, the lesson study has been carried out and investigated in several countries around the world. In this article, we strive to identify and discuss aspects related to the professional learning of mathematics teachers, developed or deepened in research that focuses on lesson study. Our analysis is made on a set of 32 works on the subject, selected from high impact journals, indexed in Scopus, which examine the possibilities and contributions of lesson study to the professional development of teachers who teach mathematics. We evidence, through a qualitative analysis, that the participation in lesson study provides the participants with professional learning in three central domains: Mathematics, mathematics teaching, and professional culture. Such learning promotes the professional development of teachers favoring changes in their professional practices, dispositions, values, and knowledge.